Risk-adjusted capital allocation and misallocation - David, Joel M.; Schmid, Lukas; Zeke, David (Journal of Financial Economics, 2022)
We develop a theory linking “misallocation,” i.e., dispersion in marginal products of capital (MPK), to macroeconomic risk. Dispersion in MPK depends on (i) heterogeneity in firm-level risk and (ii) the magnitude of risk premia. Stock market-based measures imply that risk considerations explain about 25% of MPK dispersion among US firms and rationalize a large persistent component in firm-level MPK, consistent with the micro-level data. Time-varying risk premia lead to countercyclical MPK dispersion alongside procyclical capital reallocation. Risk-based MPK dispersion in part shapes the dynamic behavior of aggregate productivity, namely, its long-run level, volatility and skewness.